Seasonal variation in eddy activity and associated heat/salt transport in the Bay of Bengal based on satellite, Argo, and 3D reprocessed data - W. Cui; W. Cui; J. Zhang; J. Yang (Ocean Science, 2022)
Based on satellite altimetry data spanning over 26 years in combination with Argo profile data or three-dimensional (3D) reprocessed thermohaline fields, the eddy synthesis method was used to construct vertical temperature and salinity structures of eddies in the Bay of Bengal, and the seasonal thermohaline properties of eddies and the heat and salt transport by eddies were analyzed. Analysis revealed that mesoscale eddy activities and the vertical thermohaline structures in the Bay of Bengal have evident seasonal variation. Temperature anomalies caused by eddies are usually between ±1 and ±3 ∘C (positive for anticyclonic eddies (AEs) and negative for cyclonic eddies (CEs)), and the magnitude varies seasonally. Salinity anomalies caused by eddies are small and disturbance signals in the southern bay due to the small vertical gradient of salinity there; salinity anomalies in the northern bay are generally between ±0.2 and ±0.3 psu, negative for AEs and positive for CEs. Owing to seasonal changes in both the eddy activity and the vertical thermohaline structure in the Bay of Bengal, the eddy-induced heat and salt transport in different seasons also changes substantially. Generally, high heat and salt transport is concentrated in eddy-rich regions, e.g., the western, northwestern, and eastern parts of the bay, the seas to the east of Sri Lanka, and the region to the southeast outside of the bay. The southern part of the bay shows weak salt transport owing to the inconsistent salinity signal within eddies. The result of the divergence of eddy heat transport illustrates that the 10–20 W m−2 value of the eddy-induced heat flux is comparable in magnitude with the annual mean air–sea net heat flux in the Bay of Bengal. Compared with the large-scale net heat flux and freshwater flux at the surface, the eddy-induced heat/freshwater transport can contribute substantially to regional and basin-scale heat/freshwater variability. This work provides data that could support further research on the heat and salt balance of the entire Bay of Bengal.